PERANCANGAN DAN PENGEMBANGAN APLIKASI HOSPITAL MOBILE BERBASIS ANDROID - Joshua .; Ignatius Barnabas Darongke; Yohanes Denny Agus Salim; Indrajani .; Raymond Bahana; Ida Bagus Kerthyayana Manuaba (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2020)
Mobile applications are computer programs that have many benefits, such as making it easier forusers to obtain and disseminate information. The mobile application can also be used to help patientsconnect with hospitals. Some of the problems faced by patients are the difficulty of contactinghospitals to register for treatment or consultation, also the difficulty of patients finding informationabout doctor's practice schedules and information about polyclinic and existing facilities so patientsmust come to the hospital to find out that information. Based on the analysis of the problem, it isproposed making a mobile application with some features needed by patients. The design andmanufacture of this application is divided into three parts, namely database using MySQL, webapplications using PHP and mobile applications using Android. Based on respondent data, it can beconcluded that this application has several uses for respondents.